Macroeconomic Determinants of Remittance Volatility: An Empirical Test. (17th May 2013) - Jackman, Mahalia
Abstract: Over the last three decades, the world has witnessed an unparalleled rise in remittances. Given the scale, trend and potential impact of these flows, several researchers have focused on determining the factors influencing remittance behaviour. But, while several studies exist on the determinants of remittances at both the microeconomic and macroeconomic levels, the literature has been largely silent on the factors influencing remittance volatility. Using a panel of 93 countries, it is found that altruistic factors (such as the age dependency ratio and the standard of living), insurance motives (captured by economic shocks at home and natural disasters), portfolio variables (interest rate volatility and exchange rate volatility), the share of skilled migrants and economic volatility in the sending country all have significant impacts on remittance volatility. However, significant differences exist across the various country groupings. This may suggest that cross‐country studies based on average behavior can conceal differences in remittance behavior across regions and can even lead to erroneous conclusions.